2017
DOI: 10.1039/c7ta08859k
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics enhancement of lithium–sulfur batteries by interlinked hollow MoO2 sphere/nitrogen-doped graphene composite

Abstract: This communication reports an interlinked MoO2 and N-rGO composite as sulfur host for high-performance lithium sulfur battery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 47 publications
2
46
0
Order By: Relevance
“…[75] Fitting the Nyquist plots at different voltages, the value change of R and CPE was investigated. As shown by previous report, [49] it is demonstrated that the condign frequency at 45° was associated with resistive/capacitive resistance. That is to say, with the fade of electrons accumulation in S1, the charge impedance was reduced.…”
Section: Exploring the Kinetics And Structure Change Of Ni-pr C-nisesupporting
confidence: 68%
See 2 more Smart Citations
“…[75] Fitting the Nyquist plots at different voltages, the value change of R and CPE was investigated. As shown by previous report, [49] it is demonstrated that the condign frequency at 45° was associated with resistive/capacitive resistance. That is to say, with the fade of electrons accumulation in S1, the charge impedance was reduced.…”
Section: Exploring the Kinetics And Structure Change Of Ni-pr C-nisesupporting
confidence: 68%
“…In the potential of 3.0-0.5 V, it is found that NiSe 2 /N-C delivered the initial discharge/charge capacity of 446.9/416.3 mAh g −1 with coulombic efficiency (CE, 93%), while that of C-NiSe 2 , P-NiSe 2 shown 421. Benefitting from the experience of Na-S battery system, it can be deduced that the NiOC bonds facilitated the trapping of polyselenide, [48,49] effectively remaining the highest residual capacity of NiSe 2 /N-C. Moreover, the CE of P-NiSe 2 was lowest, which is attributed to more exposure of surface area.…”
Section: Exploring the Electrochemical Properties Of Ni-pr C-nise 2 mentioning
confidence: 93%
See 1 more Smart Citation
“…Fabrication of TiO 2 QDs@MXene/S Cathode : The TiO 2 QDs@MXene/S cathode was fabricated by a simple melting‐diffusion method as reported by us previously . Briefly, the TiO 2 QDs@MXene nanohybrids and sublimed sulfur powder (99.99%, Aladdin S106613) were homogeneously mixed at a weight ratio of 2:8 by milling.…”
Section: Methodsmentioning
confidence: 99%
“…[107] Additionally,s trong SÀO binding interactions betweens ulfur and the MoO 2 matrix, as well as the mesoporousa rchitecture, can suppress the dissolution of lithium polysulfides, thus providing the MoO 2 /S composite cathode with ah ighc apacity,e xcellent cycling stability, and fast charget ransfer at the surface of mesoporous MoO 2 . [108] In this composite, the MoO 2 hollow structure and nitrogen-dopedr GO could hold lithium polysulfides throughb oth chemical and physical adsorption,t hus improving the cycling capability.F urthermore, the combination of MoO 2 and nitrogen-doped rGO can accelerate charget ransfer,a nd thus, improvet he kinetics of the as-assembled Li-S batteries. [108] In this composite, the MoO 2 hollow structure and nitrogen-dopedr GO could hold lithium polysulfides throughb oth chemical and physical adsorption,t hus improving the cycling capability.F urthermore, the combination of MoO 2 and nitrogen-doped rGO can accelerate charget ransfer,a nd thus, improvet he kinetics of the as-assembled Li-S batteries.…”
Section: Molybdenum Oxides For Novel Batteriesmentioning
confidence: 99%